Decoding working memory of stimulus contrast in early visual cortex - Xing, Yue; Ledgeway, Tim; McGraw, Paul V.; Schluppeck, Denis (Society for Neuroscience, 2013)
Most studies of the early stages of visual analysis (V1-V3) have focused on the properties of neurons that support processing of elemental features of a visual stimulus or scene, such as local contrast, orientation, or direction of motion. Recent evidence from electrophysiology and neuroimaging studies, however, suggests that early visual cortex may also play a role in retaining stimulus representations in memory for short periods. For example, fMRI responses obtained during the delay period between two presentations of an oriented visual stimulus can be used to decode the remembered stimulus orientation with multivariate pattern analysis. Here, we investigated whether orientation is a special case or if this phenomenon generalizes to working memory traces of other visual features. We found that multivariate classification of fMRI signals from human visual cortex could be used to decode the contrast of a perceived stimulus even when the mean response changes were accounted for, suggesting some consistent spatial signal for contrast in these areas. Strikingly, we found that fMRI responses also supported decoding of contrast when the stimulus had to be remembered. Furthermore, classification generalized from perceived to remembered stimuli and vice versa, implying that the corresponding pattern of responses in early visual cortex were highly consistent. In additional analyses, we show that stimulus decoding here is driven by biases depending on stimulus eccentricity. This places important constraints on the interpretation for decoding stimulus properties for which cortical processing is known to vary with eccentricity, such as contrast, color, spatial frequency, and temporal frequency.